DAYTIME SLEEPINESS - UNAPPROVED COMPLAINT - Івчина, Надія (SWorldJournal, 2023)
The article deals with the problem of underestimating the clinical significance of the widespread complaint of patients - daytime sleepiness. The importance of using the STOP BANG, Efort, Berlin questionnaire in the practice of a doctor of any specializat